2016
DOI: 10.1021/acs.analchem.5b04441
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Deposits Target Efficient Near-Infrared Fluorescent Probes: Synthesis, in Vitro Evaluation, and in Vivo Imaging

Abstract: The formation of extracellular amyloid-β (Aβ) plaques is a common molecular change that underlies several debilitating human conditions, including Alzheimer's disease (AD); however, the existing near-infrared (NIR) fluorescent probes for the in vivo detection of Aβ plaques are limited by undesirable fluorescent properties and poor brain kinetics. In this work, we designed, synthesized, and evaluated a new family of efficient NIR probes that target Aβ plaques by incorporating hydroxyethyl groups into the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 27 publications
4
71
0
2
Order By: Relevance
“…For enhanced fluorescence detection and imaging of pathologic Aβ aggregates in AD brain tissue, for example, conjugation to near-infrared (NIR) fluorophores or quantum dots could prove ideal, 30 as there is little to no tissue autofluorescence in the far-red or NIR regions of the electromagnetic spectrum. 42, 43 …”
Section: Resultsmentioning
confidence: 99%
“…For enhanced fluorescence detection and imaging of pathologic Aβ aggregates in AD brain tissue, for example, conjugation to near-infrared (NIR) fluorophores or quantum dots could prove ideal, 30 as there is little to no tissue autofluorescence in the far-red or NIR regions of the electromagnetic spectrum. 42, 43 …”
Section: Resultsmentioning
confidence: 99%
“…The author further replaced benzene ring of DANIR-2c with naphthalene ring to synthesize DANIR-3c ( Figure 5), and the fluorescence emission wavelength was beyond 680 nm. [53] DANIR-8c performed better binding ability toward Adv Aβ aggregates, hydrophilicity, and brain kinetics. Toward this issue, the author introduced incorporating hydroxyethyl groups into the N,N-dimethyl moiety of DANIR-3c to synthesize the compound DANIR-8c ( Figure 5).…”
Section: The Detection Of Aβ Aggregatesmentioning
confidence: 95%
“…The experiments on fibrillar amyloids of hen egg white lysozyme showed that PD‐NA‐TEG had the best detection capability with a low limit of detection (LOD) of 63.71 × 10 −9 m . Moreover, these AIEgens, especially PD‐NA and PD‐NA‐TEG, exhibited excellent binding capacities to Aβ plaques in the mouse brain, as revealed by the overlapped images of them with 8C (a reported probe for β‐amyloid plaques) (red spots, Figure B). More importantly, ex vivo super‐resolution imaging of Aβ plaques in brain slices has also been successfully conducted to resolve the specific morphology in detail (Figure C–E).…”
Section: Disease Diagnosismentioning
confidence: 95%